Study on wind-sand dynamics observation of blowout in Xilingol sandy grassland - Gao, Tianxiao; Gao, Yong; Huang, Luxi; Yang, Juan; Yang, Wenyuan; Guo, Xiaoyu (Frontiers in Environmental Science, 2024)
This study investigated airflow changes and sediment transport in the blowouts of the sandy grassland in Xilingol, Inner Mongolia.The results show that the wind direction inside the blowout is influenced by the direction of the incoming wind. Specifically, when the angle between the incoming wind direction and the long axis of the blowout is less than 15°, both sides of the wall tend to generate a wind flow towards the east exit. Meanwhile, the main airflow along the central axis airflow deflects towards the north side wall. However, when the angle is greater than 15°, the airflow on the north wall first disperses and then converges towards the wellbore. Conversely, the airflow on the south wall blows out in a southeast direction, and the axial airflow deflects towards the south wall.The rate of wind speed acceleration on both sides of the wall increases with height within the blowout but decreases along the central axis section. Higher wind speeds correlate with greater cumulative sand transport heights. Sand transport heights on both sides of the deflation basin are smaller than those along the central axis section, with the opposite observed in the depositional lobe. The rate of sand transport is primarily influenced by wind direction and wind speed, followed by , topography, vegetation coverage, slope, and aspect.These variations in airflow, combined with sediment transport,lead to the blowout taking on a develop deeper, longer, and wider shape.Blowouts, as defined, are concave or depressed formations resulting from wind erosion (Hesp, 2002;Wang et al., 2007). They commonly manifest as wind erosion craters on sandy coasts, lakeshores, sandy grasslands, and inland sandy lands within semi-arid and partly semi-humid regions (